Accounting information and internal performance evaluation - Blackwell, David W.; Brickley, James A.; Weisback, Michael S. (Journal of Accounting and Economics, 1994)
Multi-bank holding companies file detailed financial statements on their subsidiary banks. The availability of these data allows for an empirical examination of the relation between accounting-based performance and personnel decision for lower-level managers. For our sample of Texas banks, we find that turnover of subsidiary bank managers is negatively related to subsidiary performance, while promotions are positively related to performance. Holding own-bank performance constant, turnover increases with holding-company performance, which is consistent with the view that turnover decisions are based on performance relative to a firm-specification benchmark.